'Eco this and recycle that': an ecolinguistic analysis of a popular digital simulation game. Issue 3 (26th May 2020) - Poole, Robert; Spangler, Sydney
ABSTRACT: This article presents an ecolinguistic analysis of a popular digital simulation game, Animal Crossing: New Leaf (2012). As the popularity and immersive capability of digital gaming continues to expand, there is need for investigations of how digital games may either perpetuate ecologically destructive ideologies, practices, and identities or promote and cultivate more ecologically sustainable options. The simulation game genre is of particular interest as these games are typically designed to reproduce and reflect real world activities in which gamers complete tasks for purposes such as education, training, and entertainment. Although elements of the Animal Crossing: New Leaf game may be viewed as promoting sustainable ecological action and fostering identities and practices supportive of ecological wellbeing and sustainability, game features and operations central to play within the constructed game world reflect, normalize, reproduce, and perpetuate the production and performance of identities and human-nature relationships at the root of the ecological crisis.